2010
DOI: 10.1126/science.1195055
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Gold/Water Interface During Selective Oxidation Catalysis

Abstract: The selective oxidation of alcohols in aqueous phase over supported metal catalysts is facilitated by high-pH conditions. We have studied the mechanism of ethanol and glycerol oxidation to acids over various supported gold and platinum catalysts. Labeling experiments with (18)O(2) and H(2)(18)O demonstrate that oxygen atoms originating from hydroxide ions instead of molecular oxygen are incorporated into the alcohol during the oxidation reaction. Density functional theory calculations suggest that the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

67
1,023
4
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 981 publications
(1,107 citation statements)
references
References 35 publications
67
1,023
4
13
Order By: Relevance
“…Consistent with the previous experimental [21][22][23] and theoretical results [31][32][33], the computed E ad value of −0.09 eV indicates very weak binding between the molecular methanol and the Au surface. This unfavorable interaction may account for observed low activity of clean Au surface for methanol oxidation.…”
Section: Interactions Between Adsorbates and Au(1 1 1)supporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the previous experimental [21][22][23] and theoretical results [31][32][33], the computed E ad value of −0.09 eV indicates very weak binding between the molecular methanol and the Au surface. This unfavorable interaction may account for observed low activity of clean Au surface for methanol oxidation.…”
Section: Interactions Between Adsorbates and Au(1 1 1)supporting
confidence: 78%
“…To the best of our knowledge, so far few theoretical efforts have been made with the exact purpose of disclosing the crucial reaction mechanisms of alcohol oxidation on Au(1 1 1) surface [31][32][33]. Previously, Xu et al studied the reaction mechanism for methanol oxidation on a oxygen-covered Au(1 1 1) surface by using density functional theory (DFT) method and pointed out that both methanol and methoxy were activated by oxygen adatoms [33].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Shang et al calculated the adsorption energy of OH − ions, as 30 kJ/mol, which has the same magnitude order as that obtained in this work, although the values were different. Zope et al [29] also reported that GLY oxidation by adsorbed OH − species was more energetically favourable than by dissolved ones. Moreover, they asserted that the role of O 2 during alcohol oxidation is an indirect one that does not involve a reaction to form the acid products, but a reduction to form the hydroperoxide adduct OOH − , this is in agreement with the kinetic model proposed in the present work.…”
Section: Discussionmentioning
confidence: 96%
“…For benzyl alcohol oxidation, the 4% Pd@C-Glu A -550 was found to be indeed more active than 4% Pd@C-Glu-550 (Supplementary Table S5), partly supporting the proposed assumption. In addition, it was reported that the basic support can improve the formation of alcoholate by means of O-H scission in the liquidphase alcohol oxidation reaction 52 . As a typical basic support, C-Glu A -550 may contribute to O-H scission in the alcohol oxidation, thus promoting the oxidation to some degree.…”
Section: Discussionmentioning
confidence: 99%